Ab initio water hexamers and octamers: tool to study hydrogen-bonded pattern in liquid water - Kryachko, E. (Condensed Matter Physics, 1998)
Fourteen different structures of water hexamer found ab initio within a 6- 311G** basis set in the interval of 1.7 kcal/mol above the global minimum represent an unprecedently wide range of conformational plasticity of liquid water. The present work also provides the first ab initio demonstration of the existence of pentacoordinated water clusters.